PENGARUH LINGKUNGAN KELUARGA DAN LINGKUNGAN SEKOLAH TERHADAP PRESTASI BELAJAR SISWA EKONOMI KELAS XI IPS SMU N 10 KOTA JAMBI - Harbeng Masni, Lili Andriani (Universitas Batanghari Jambi, 2017)
AbstrakThe environment always revolves around the human from the time of birth until death, so that between the environment and humans there is a reciprocal relationship in the sense that the environment affects humans and humans affect the environment. So is the new as a whole, as its own experience in interaction with its environment